Turn-taking and gender differences in language classroom - Azhar, Kaukab Abid; Iqbal, Nayab (Journal of NELTA, 2018)
The study aims at studying gender differences in the ways male and female students take turns and participate in a mixed-gender classroom. Two groups of first-year English compulsory classes held at two different departments (Geography and Economics) at the University of Karachi took part in the study. The results revealed that in the Geography Department, where there was a female teacher, male students were more dominating as compared to the female students who hardly participated in the class. They took more turns and participated better in the classroom discussion. In addition, they also interrupted the teacher and the female counterparts when they tried to contribute to the discussion. On the other hand, at the Department of Economics, female students had more number of turns. They dominated the classroom as compared to the male students. Besides, the study revealed that the gender of the teacher played an important part in shaping the discourse taking place in the classroom.